2021
DOI: 10.1177/2057158520988452
|View full text |Cite
|
Sign up to set email alerts
|

Support and resources to promote and sustain health among nurses and midwives in the workplace: A qualitative study

Abstract: Registered nurses and midwives are in short supply and have among the highest rates of sick leave in the global workforce. The aim of this study was therefore to explore and gain a deeper understanding of how nurses and midwives experience their everyday work, with a view toward promoting and sustaining their work-related health. Nine registered nurses and four registered midwives working in hospitals and community healthcare facilities in Sweden were interviewed. The interviews were analyzed using content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For sustainability and to maintain the health of nursing professionals, employers should adopt a systematic approach. This includes minimizing workloads and offering opportunities for supervision and reflection, which can be achieved through managerial and social support in the workplace [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sustainability and to maintain the health of nursing professionals, employers should adopt a systematic approach. This includes minimizing workloads and offering opportunities for supervision and reflection, which can be achieved through managerial and social support in the workplace [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although its demands are high and there is a high prevalence of stress and burnout, the nursing profession is associated with high work engagement [ 23 , 24 ]. Without the physical involvement, cognitive alertness, and emotional connection of health professionals, especially nurses, patients could not be provided with sufficient quality of care [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study participants indicated that lack of appreciation from nursing managers was of concern; this made them feel demotivated, and their contribution to maternity care was not valuable. According to Matlala and Lumadi (34), managers do not appreciate the midwives' challenges in maternity units. Thapa et al (35) added to these ndings and found that midwives shared they yearn for their managers to display interest in their work, provide their opinions and be more appreciative.…”
Section: Sub-theme 13: Lack Of Appreciationmentioning
confidence: 99%
“…When implementing a new clinical practice involving midwives it is important that it is acceptable to both the women who are giving birth and the midwives 17 . Understanding midwives' experiences and preferences is vital to implementing sustainable, high‐quality clinical care 18 . In order to further study experiences of this clinical practice, the aim of this study was to investigate primary midwives' experiences of collegial midwifery assistance with the purpose of preventing SPT during the active second stage of labor.…”
Section: Introductionmentioning
confidence: 99%